Evidence for Local Regulatory Control of Escape from Imprinted X Chromosome Inactivation. Issue 2 (1st June 2014) - Mugford, Joshua W; Starmer, Joshua; Williams, Rex L; Calabrese, J Mauro; Mieczkowski, Piotr; Yee, Della; Magnuson, Terry
Abstract: X chromosome inactivation (XCI) is an epigenetic process that almost completely inactivates one of two X chromosomes in somatic cells of mammalian females. A few genes are known to escape XCI and the mechanism for this escape remains unclear. Here, using mouse trophoblast stem (TS) cells, we address whether particular chromosomal interactions facilitate escape from imprinted XCI. We demonstrate that promoters of genes escaping XCI do not congregate to any particular region of the genome in TS cells. Further, the escape status of a gene was uncorrelated with the types of genomic features and gene activity located in contacted regions. Our results suggest that genes escaping imprinted XCI do so by using the same regulatory sequences as their expressed alleles on the active X chromosome. We suggest a model where regulatory control of escape from imprinted XCI is mediated by genomic elements located in close linear proximity to escaping genes.